Comments on reconstitution of biocultural development of prehistoric populations - Piontek, Janusz; Czerniak, Lech (Anthropological Review, 1980)
In culturological studies a return of evolutionary idea may be observed. New concepts of cultural ecology conceive the process of cultural transformations as a sequence of changes displaying adaptive character, This approach assumes that factors of biological and of cultural development operate in mutual interrelation forming general pattern of biocultural evolution. Precise ascertainment of respective influence of biological and of cultural factors requires such a simplification of a subject of studies that ensures their effective distinction. In order to study biological changes physical anthropology has elaborated a number of methods: for either reconstitution or description of individual and populational characteristics. These are the variables describing basic biological properties of populations in a uniform way irrespective of territory, time period and cultural system to which a given human group is related. Cultural characteristics that can be reconstituted for prehistoric populations on grounds of archaeological investigations usually are not of such a universal nature. Archeology almost always uses characteristics describing properties of a given, concrete cultural system. This situation prevents performance of analyses of evolutionary kind. One of the measures of the biocultural evolution may be a characteristics of exploitative efficiency (K) that could be described on grounds of information upon nutritional capacity of environment (S), habitat capacity (P), human group size (L) and size of the habitat economically exploited by a human group (microregion) — M. Exploitative efficiency of a group (K) may be expressed by actual population density of people representing a given cultural system in a given period and within defined natural environment. Habitat capacity (P) informs in turn about maximum (relative to ecological equilibrium) attainable population density that a population of a given exploitative efficiency can reach under given environmental conditions. Knowledge upon relations. between variables K and P is necessary for reconstitution of  internal behavior of cultural systems i.e. in order to explain ecological content of transformations of cultural systems. Yet for more general investigations (ones concerning intergroup relations) it is sufficient to know solely values of exploitative efficiency. This seems to be easily attinable in studies on prehistoric populations. A clue problem in the type of studies dealth with here is distinction of a microregion constituting the main cultural variable. Therefore in the paper are described problems concerning rules for transformation of archaeological data (so called archaeometic data) into historical ones (cultural variables) directly useful for calculations of population density in settlement microregionis.